The structural, electronic, elastic, thermodynamic, magnetic, and optical properties of the yttrium-based full-Heusler alloys Y2CrZ (Z=Si, Ge, Sn). (August 2018) - Kang, Xu-Hui; Zhang, Jian-Min
Abstract: The structural, electronic, elastic, thermodynamic, magnetic, and optical properties of yttrium-based full-Heusler alloys of the form Y 2 CrZ (Z = Si, Ge, Sn) have been studied by first-principles calculations. The stable half-metallic ferrimagnetic characters, which are maintained in the lattice constant ranges 6.365–7.057 Å ( Y 2 CrSi ), 6.496–7.163 Å ( Y 2 CrGe ), and 6.515–7.385 Å ( Y 2 CrSn ), ensure their potential application in spintronics and magnetoelectronics. The total magnetic moment of 2 μB per formula unit satisfies the Slater-Pauling rule M t = 18 - Z t . The formation energy E f, cohesion energy E c, spin-up band gap E g ↑, shear modulus G, bulk modulus B, Young's modulus E, Debye temperature Θ D, melting temperature T melt, static dielectric constant ε 1 ( 0 ), maximum imaginary part of the dielectric constant ε 2 ( ω ) max, maximum reflective index R ( ω ) max, and static refractive index n ( 0 ) decrease for Y 2 CrSi, Y 2 CrGe, and Y 2 CrSn successively. Increases in both Poisson's ratio υ and Pugh's ratio B / G indicate the ductile character increases for Y 2 CrSi, Y 2 CrGe, and Y 2 CrSn successively. The highest global maximum value in the energy loss function L ( ω ) spectra of these three alloys indicates that Y 2 CrSn is the most suitable material to make a far-ultraviolet photodetector. Graphical abstract: The total density of states (DOS) (black) and partial DOS projected onto Y1 4d (red), Y2 4d (blue), Cr 3d (green), and Si/Ge/Sn p (magenta) orbitals for the full-Heusler alloys of the form Y2 CrZ (Z=Si, Ge, Sn) in the Hg2 CuTi structure ferrimagnetic state with the equilibrium lattice constants. The positive and negative values represent the spin-up and spin-down channels, respectively. The Fermi level EF was set at zero energy and is indicated by vertical solid red lines. Highlights: The stable half-metallic ferrimagnetic natures of alloys of the form Y2 CrZ (Z=Si, Ge, Sn) ensure their spintronics applications. The half-metallic natures of alloys of the form Y2 CrZ (Z=Si, Ge, Sn) are maintained in the lattice constant ranges 6.365-7.057 Å, 6.496-7.163 Å, and 6.515-7.385 Å, respectively. Th total magnetic moment of 2 μB per formula unit satisfies the Slater-Pauling rule Mt =18-Zt . Ef, Ec, E g ↑, G, B, E, Θ D, Tmelt, ε ( 0 ), ε 2 ( ω ) max, R ( ω ) max, and n(0) decrease for Z=Si, Ge, and Sn successively. The highest ν, B/G, and L ( ω ) show Y2 CrSn is the most ductile material and most suitable material to make a far-ultraviolet photodetector.